Characteristics of dynamic mechanics and energy loss in reef limestone concrete during dry-wet carbonation periods - Li, Jian; Li, Fei; Mao, Mingju; Zhang, Jinrui; Fan, Ran (Frontiers in Materials, 2024)
The coral reef limestone, as a special type of rock and soil body, has a high porosity. Under the impact load, the dynamic mechanical properties of coral reef limestone concrete exhibit significant differences compared to conventional land-sourced aggregate concrete. This study uses coral reef limestone as coarse and fine aggregate to prepare C40 strength concrete and investigates the effects of dry-wet carbonation cycles on its dynamic mechanical behavior and energy evolution characteristics using the SHPB mechanical testing system. The results indicate that as the number of dry-wet carbonation cycles increases, the bonding degree of the internal structure of the coral reef limestone concrete significantly weakens, the degree of phenolphthalein color change gradually diminishes, and both the uniaxial compressive strength and tensile strength show an overall downward trend. Furthermore, the reduction in tensile strength is less pronounced than that of compressive strength, the relative dynamic elastic modulus gradually decreases, and a size effect is observed, with the rate of mass loss accelerating rapidly. As the number of dry-wet carbonation cycles increases, the dynamic compressive strength decreases, and the failure mode transitions from surface cracking to crush-type failure. The DIF value of the coral reef limestone concrete indicates a high sensitivity to strain rate, meaning the DIF value rises significantly with increasing strain rate.Various energies generated under impact load exhibit clear strain rate effects, and the effects of drywet carbonation cycling facilitate energy dissipation, particularly when the number of cycles reaches 30, at which point energy dissipation increases sharply, while there is a hindering effect on transmitted energy.